2008
DOI: 10.1614/ws-07-167.1
|View full text |Cite
|
Sign up to set email alerts
|

Liverwort (Marchantia polymorpha) Response to Quinoclamine in a Pine Bark Substrate

Abstract: Quinoclamine is an herbicide under development for control of liverwort, a weed common in nursery crops. With respect to liverwort control, quinoclamine has been considered to primarily have POST activity. However, some PRE activity has been reported. Growth media sorption studies with14C-quinoclamine indicate that only 0.64% of the quinoclamine amount that enters the media remains unadsorbed and thus available to be taken up by established plants or propagules. Computer modeling revealed that a large portion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Some of those chemicals, such as iodomethane reached a 100% weed control efficacy (Fennimore et al, 2008). Later, herbicides, such as oryzalin, glyphosate, flumioxazin, oxyfluorfen, pendimethalin, isoxaben, trifluralin, and their combinations become more widely tested, other herbicides that have both preemergence and postemergence effects, such as quinoclamine was also tested in different studies (Porter, 1996;Willoughby et al, 2003;Altland et al, 2004Altland et al, , 2007Altland et al, , 2008Altland et al, , 2011Awan et al, 2006;Judge and Neal, 2006;Qasem, 2006Qasem, , 2007Richardson and Zandstra, 2009;Wehtje et al, 2010aWehtje et al, ,b, 2012Rahman et al, 2011;Abit and Hanson, 2013;Ramalingam et al, 2013;Vasic et al, 2015;Marble et al, 2016b). Most of the herbicides, such as oxadiazon, flumioxazin, and prodiamine, presented satisfactory weed control performances (Judge and Neal, 2006;Amoroso et al, 2009;Wehtje et al, 2010a).…”
Section: Research Trend In Nursery Weed Controlmentioning
confidence: 99%
“…Some of those chemicals, such as iodomethane reached a 100% weed control efficacy (Fennimore et al, 2008). Later, herbicides, such as oryzalin, glyphosate, flumioxazin, oxyfluorfen, pendimethalin, isoxaben, trifluralin, and their combinations become more widely tested, other herbicides that have both preemergence and postemergence effects, such as quinoclamine was also tested in different studies (Porter, 1996;Willoughby et al, 2003;Altland et al, 2004Altland et al, , 2007Altland et al, , 2008Altland et al, , 2011Awan et al, 2006;Judge and Neal, 2006;Qasem, 2006Qasem, , 2007Richardson and Zandstra, 2009;Wehtje et al, 2010aWehtje et al, ,b, 2012Rahman et al, 2011;Abit and Hanson, 2013;Ramalingam et al, 2013;Vasic et al, 2015;Marble et al, 2016b). Most of the herbicides, such as oxadiazon, flumioxazin, and prodiamine, presented satisfactory weed control performances (Judge and Neal, 2006;Amoroso et al, 2009;Wehtje et al, 2010a).…”
Section: Research Trend In Nursery Weed Controlmentioning
confidence: 99%
“…Another chemical, quinoclamine (Gentry; Chemtura Corp., Middlebury, CT) has shown 96% postemergence control at 2 d after treatment (DAT) and 94% control at 45 DAT to mature common liverwort (Altland et al, 2003). Altland et al (2008) also studied the response of common liverwort to the herbicide quinoclamine in a medium containing pine bark. Quinoclamine provided preemergent control of gemmae propagules as well as contributed to postemergent control of established common liverwort.…”
Section: Overview Of Chemical Control Of Common Liverwortmentioning
confidence: 99%
“…In each of the two constant temperature regimes (22.6 ± 1.7°C in the warm room, 12.3 ± 0.6°C in the cold room), sciarid larvae damaged the M. polymorpha thalli by tunneling and feeding on the chlorophyllous tissue. The three-way ANOVA revealed that area of damage was very highly signifi cantly is frequently a serious weed as it is a strong competitor for water and nutrients during propagation of horticultural and ornamental plants (Cronberg, 1990(Cronberg, , 1991Svenson, 2000;Fausey, 2003;Newby et al, 2007;Altland et al, 2008). The dispersal and spread of this liverwort can be reduced to some extent by a number of hygienic measures such as the use of clean pots and modifi ed cultivation techniques (Cronberg, 1990(Cronberg, , 1991.…”
Section: Effect Of the Feeding Of Sciarid Larvae On Liverwort Thallusmentioning
confidence: 99%